Method for detecting mechanical properties of an open-cell foam-based interpenetrating phase composite
Patent Information
- Application Number
- CN202411384922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-09-30
AI Technical Summary
(2)3D断层扫描重构模型,此种模型建模方法是对泡沫材料胞孔结构的真实复现,甚至能重建出材料内部存在小的孔洞、裂缝等缺陷,但由于3D断层扫描需要高精度扫描设备、复杂的图像处理算法以及需要专业人员进行大量的后期数据处理工作,使得时间、人工成本均较高,且生成的模型不能直接用于有限元计算,模型中过于精细的部分难以划分网格,还需采用图形处理软件对模型进行理想化处理,整个流程十分复杂
[0051](1)本发明1.1步对需要检测的开孔泡沫基互穿相复合材料进行建模,检测时是针对与应用场景相一致的开孔泡沫基互穿相复合材料模型,不需要真正制备开孔泡沫基互穿相复合材料,也不需要特殊的实验装置以及具有专业技术的实验人员,一方面可以在很大程度上节约时间成本和劳动成本,提高检测效率,另一方面,检测不受开孔泡沫基互穿相复合材料制备工艺、实验装置及实验操作误差、环境等因素的影响,减少了测试误差。
Smart Images

Figure CN119230030B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of mechanical property testing technology for interpenetrating phase composite materials, and specifically to a method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials. Background Technology
[0002] In the fields of aviation, aerospace, and shipbuilding, the protective structures of key components (such as engines and their key parts, power systems, and electronic equipment) are generally made of a single material (i.e., steel, aluminum, etc.). Single-material structures are simple in structure but have poor corrosion resistance and heat resistance, and cannot meet the specific requirements of certain environments. Open-cell foam-based interpenetrating phase composite materials can overcome the shortcomings of single materials. In practical engineering, there is an increasing need for lightweight, high-strength, high-toughness, and functionally dual-purpose materials. Open-cell foam-based interpenetrating phase composite materials have broad application prospects in aviation, aerospace, transportation, energy, and construction. As a multiphase material, open-cell foam-based interpenetrating phase composite materials possess topological continuity, interconnectivity, and isotropy, exhibiting unique mechanical properties (such as excellent impact resistance, good heat and corrosion resistance, adjustable coefficient of thermal expansion, and excellent fatigue life). These properties are superior to traditional composite materials simply composed of different materials. At every stage of application, open-cell foam-based interpenetrating phase composite materials synergistically contribute their characteristics to the overall multifunctionality of the material. For example, if one component of an open-cell foam-based interpenetrating phase composite provides toughness and strength, another component may provide thermal stability, abrasion resistance, shock resistance, or damping properties. These two components can be considered separate parts existing in space, each permeating the entire interpenetrating phase composite in its spatial dimension. Because the components of the open-cell foam-based interpenetrating phase composite are interconnected in three-dimensional space and intertwined in all directions, the interfacial volume ratio is quite high, thus enabling it to satisfy both certain mechanical properties and functional requirements.
[0003] In the design and manufacturing process of open-cell foam-based interpenetrating phase composites, experiments are generally used to determine whether the designed and produced open-cell foam-based interpenetrating phase composites meet the mechanical performance requirements of practical applications (i.e., toughness, strength, etc., characterized by mechanical performance parameters such as yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D). However, the microstructure and preparation process of open-cell foam-based interpenetrating phase composites are complex, posing a challenge to testing their mechanical properties. Testing the mechanical properties of open-cell foam-based interpenetrating phase composites experimentally first requires the preparation of the composite material. The internal structure of open-cell foam-based interpenetrating phase composites is complex, the preparation process is complicated, the preparation time is long, the preparation process is prone to errors, and the scrap rate is high. Simultaneously, testing equipment such as universal testing machines and Hopkinson bars are needed to experimentally test the mechanical properties of open-cell foam-based interpenetrating phase composites. The testing process requires high levels of expertise from the testing equipment and personnel, and may damage the test specimens. Therefore, it is both inconvenient and expensive to test the mechanical properties of open-cell foam-based interpenetrating phase composites using experimental methods, with high time and economic costs.
[0004] Therefore, numerical simulation is becoming an increasingly important method for detecting the dynamic mechanical behavior of open-cell foam-based interpenetrating phase composites, and is used to determine whether these composites meet application requirements. The method for detecting the mechanical properties of open-cell foam-based interpenetrating phase composites using numerical simulation mainly includes the following steps:
[0005] The first step is to construct a model of an open-cell foam-based interpenetrating phase composite material, including the following steps:
[0006] 1.1 Constructing a random porous model;
[0007] The open-cell foam-based interpenetrating phase composite material is composed of random porous models and filled phase models. Random porous models are divided into the following three types: (1) Regular geometric models, such as Gibson-Ashby model, Kelvin model, and cubic cavity model. Regular geometric models are composed of multiple identical cells arranged in a regular order in space. The shape and size of the cells are highly controllable. Therefore, the modeling process of regular geometric models is simple, the cell structure is simple, and it does not have randomness. It is quite different from the real foam structure. (2) 3D tomography reconstruction model. This modeling method is a true reproduction of the cell structure of foam materials. It can even reconstruct small holes, cracks and other defects inside the material. However, because 3D tomography requires high-precision scanning equipment, complex image processing algorithms and a lot of post-processing work by professionals, the time and labor costs are high. Moreover, the generated model cannot be directly used for finite element calculation. The overly fine parts in the model are difficult to mesh. It is also necessary to use graphics processing software to idealize the model. The whole process is very complicated. (3) Random evolution model. The Voronoi model is widely used. This modeling method divides the space into a series of polygonal regions, each containing a discrete point (called a "seed point"). Different foam materials with different structures can be generated by controlling the number of seed points, the minimum distance between seed points, and the wall thickness. It has strong design flexibility. However, it can only realistically reflect the closed-cell foam structure with relatively low density. Also, because the cell wall is relatively thin compared to the cell pores, the generated model often has to be meshed using shell elements, which makes the finite element simulation calculation inaccurate.
[0008] 1.2 Constructing a filled phase model;
[0009] The filler phase material is filled into the pores of the random porous model, ensuring that the pores are completely filled. All the filler phase material in the pores forms a single unit, called the filler phase model. The random porous model and the filler phase model together constitute the open-cell foam-based interpenetrating phase composite material model. Taking the modeling software Rhino as an example, the specific steps are as follows: A filler phase model with the same external shape and geometric dimensions as the random porous model is constructed. The random porous model and the filler phase model are aligned on their external contours. The overlapping portion of the filler phase model with the random porous model is removed. Finally, the random porous model is combined with the remaining filler phase model after removing the overlapping portion to generate the open-cell foam-based interpenetrating phase composite material model.
[0010] The second step is to perform finite element analysis on the open-cell foam-based interpenetrating phase composite material model to obtain the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model (mainly including yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D).
[0011] The third step involves comparing the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model obtained through the finite element analysis process in the second step—yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D—with the mechanical property characterization parameters required by the application environment—yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0—to check whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model meet the requirements of the application environment. If the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material model all meet the application requirements, it indicates that the yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material model are qualified. If any one of the yield strength σ, failure stress Q, elastic modulus E, or energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, it indicates that the open-cell foam-based interpenetrating phase composite material model does not meet the mechanical performance requirements of the application environment. The open-cell foam-based interpenetrating phase composite material model needs to be adjusted, and the open-cell foam-based interpenetrating phase composite material should be designed according to the mechanical performance requirements of the application environment.
[0012] In engineering applications, the model established in the first step has many simplifications or defects compared to the real model. This leads to inaccurate calculations of the mechanical property characterization parameters of open-cell foam-based interpenetrating phase composites, such as yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, through numerical simulation. As a result, misjudgments occur when the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite model are checked in the third step. This makes it impossible to provide real-time and accurate guidance for design and production, affecting the design, optimization, and use of open-cell foam-based interpenetrating phase composites. Consequently, the protective and vibration isolation structures of key components in aerospace, automotive, and other fields may fail prematurely, causing incalculable losses. Summary of the Invention
[0013] The technical problem to be solved by this invention is to propose a method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials, which makes the mechanical property testing of open-cell foam-based interpenetrating phase composite materials accurate, saves time, and does not damage the test specimens. This allows for real-time and accurate guidance on the design and production of open-cell foam-based interpenetrating phase composite materials, enabling rapid design, optimization and use of open-cell foam-based interpenetrating phase composite materials, and saving design, production and manufacturing costs.
[0014] To achieve the above objectives, the following technical solution is adopted:
[0015] The first step is to establish a model of open-cell foam-based interpenetrating phase composite material. The process of refining the model of open-cell foam-based interpenetrating phase composite material is as follows:
[0016] 1.1 Determine the shape and size of the open-cell foam-based interpenetrating phase composite material model according to the application scenario (such as protection of engines and their key components, power systems, electronic devices, etc.). The maximum area of the open-cell foam-based interpenetrating phase composite material model is greater than or equal to the area of the largest surface of the protected electronic component. Let the volume of the open-cell foam-based interpenetrating phase composite material model determined according to the application scenario be V. m .
[0017] 1.2 Based on the open-cell foam-based interpenetrating phase composite material model, determine the volume V0 of the random porous model and the average number of pores N of the random porous model, and randomly distribute seed points within the random porous model. The method is as follows:
[0018] The geometry of the random porous model is defined as a cuboid, and its volume is defined as V0. The random porous model must be able to completely contain at least two open-cell foam-based interpenetrating phase composite material models determined according to the application scenario, i.e., V0 ≥ 2V0. m The average number of open cells per inch (ppi) of the open-cell foam matrix is determined according to the application scenario (generally ppi is 20-100), and the average number of pores N of the random porous model is determined by formula (1):
[0019]
[0020] 1.3 The number of seed points M in the 3D-Voronoi model is determined by the average number of pores N in the random porous model, i.e., M = N. (The 3D-Voronoi model is a 3D discretization method based on the Voronoi diagram. It divides the three-dimensional space into a series of polyhedral elements, each containing a discrete point (called a "seed point"). Different foam materials with different structures can be generated by controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral elements.)
[0021] 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model.
[0022] 1.5 A 3D-Voronoi model is established based on seed points randomly placed within the random porous model, and 3D-Voronoi cells are generated from the 3D-Voronoi model.
[0023] In a random porous model, each randomly distributed seed point has a surrounding space called a Voronoi cell. The distance from any point A (excluding the seed point) within a Voronoi cell to the seed point Q within the Voronoi cell is less than the distance from point A to any other seed point in the space (excluding Q). In other words, each Voronoi cell encloses only one seed point. A 3D-Voronoi model is constructed from all Voronoi cells within the random porous model. From the 3D-Voronoi model, a series of 3D-Voronoi cells can be obtained. Each 3D-Voronoi cell corresponds to a seed point in the random porous model and has a different geometry and size.
[0024] 1.6 Extract points and lines from 3D-Voronoi cells to generate a structural line model. The method is as follows:
[0025] 1.6.1 Decompose the 3D-Voronoi cell into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cell.
[0026] 1.6.2 Since adjacent 3D-Voronoi cells in the 3D-Voronoi model are in contact with each other, there are a large number of repeated intersections and lines after the 3D-Voronoi cells are decomposed into points and lines. Therefore, the repeated intersections and lines in the initial structural line model are cleaned up, that is, the repeated points and lines are deleted. The remaining intersections and lines in the initial structural line model constitute the structural line model.
[0027] 1.7 Transform the structural line model into a structural volume model, and obtain the open-cell foam material matrix from the structural volume model. The method is as follows:
[0028] 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number. In this way, the structure line in the structure line model is transformed from a line to a volume, and the structure line model is transformed into a structure volume model.
[0029] 1.7.2 Use the modeling software Rhino (version 6.0 and above) to calculate the volume V of the structural model.
[0030] 1.7.3 Calculate the theoretical volume V of the open-cell foam matrix using formula (2) n :
[0031] V n =V0×ε (2)
[0032] In the formula, ε represents the relative density of the open-cell foam material matrix, which is equal to the relative density of the open-cell foam material in the model of open-cell foam matrix interpenetrating phase composite material.
[0033] 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam matrix. n To make a comparison, if V n -V>0.5mm 3 This indicates that the volume V of the structural model is smaller than the theoretical volume V. n This requires increasing the diameter d of the structure lines in the structure line model; see section 1.7.1. If V n -V < -0.5mm 3 This indicates that the volume V of the structural model is too large, and the diameter d of the structural lines in the structural line model needs to be reduced. (See 1.7.1) If |V n -V│≤0.5mm 3 This explains the relationship between the total volume V of the structural model and the theoretical volume V of the open-cell foam material matrix. n Approximately equal, at this point, the structural model is the open-cell foam material matrix, see section 1.8.
[0034] 1.8 Construct an initial filled phase model with the same geometry and dimensions as the open-cell foam-based interpenetrating phase composite material model.
[0035] 1.9 Place the initial filled phase model at the geometric center of the open-cell foam matrix, remove the material of the open-cell foam matrix outside the initial filled phase model, and remove the material of the initial filled phase model in the part that overlaps with the open-cell foam matrix to obtain the open-cell foam matrix interpenetrating phase composite material model.
[0036] The second step involves using finite element analysis software (such as ANSYS (version 19.2 and above) or ABAQUS (version 6.14 and above)) to perform finite element analysis on the open-cell foam-based interpenetrating phase composite material model 3 constructed in the first step. The method is as follows:
[0037] 2.1 To more realistically reflect the stress state of the open-cell foam-based interpenetrating phase composite material model, an upper pressure plate is established at the contact point with the upper surface of the model, and a lower pressure plate is established at the contact point with the lower surface. The model is located at the geometric center between the upper and lower pressure plates. The upper and lower pressure plates are discs with identical geometric dimensions. The cross-sectional diameter of the upper and lower pressure plates is greater than the cross-sectional diameter of the open-cell foam-based interpenetrating phase composite material matrix, and the thickness has no special requirements.
[0038] 2.2 Finite element mesh generation was performed on the open-cell foam-based interpenetrating phase composite material model 3 and the upper and lower pressure plates. The open-cell foam-based interpenetrating phase composite material model 3 adopted a tetrahedral mesh, while the upper and lower pressure plates adopted a hexahedral mesh. The mesh was evenly distributed on the open-cell foam-based interpenetrating phase composite material model, the upper pressure plate, and the lower pressure plate.
[0039] 2.3 Constrain the motion boundaries of the upper and lower pressure plates by establishing a Cartesian coordinate system. The upper pressure plate is not allowed to have displacement in the X and Y directions, nor is it allowed to rotate in the X, Y, and Z directions. The upper pressure plate is only allowed to move in the Z direction. At the same time, the lower pressure plate is not allowed to have displacement or rotation in the X, Y, and Z directions.
[0040] 2.4 The contact between the upper pressure plate and the upper surface of the open-cell foam-based interpenetrating phase composite material model is defined as surface-to-surface contact; the contact between the lower pressure plate and the lower surface of the open-cell foam-based interpenetrating phase composite material model is defined as surface-to-surface contact; and the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating phase composite material model is defined as erosion contact.
[0041] 2.5 Determine the materials for the open-cell foam-based interpenetrating phase composite material model, upper pressure plate, and lower pressure plate according to the application scenario. The materials for the open-cell foam-based interpenetrating phase composite material model are determined based on the open-cell foam-based interpenetrating phase composite material required for the application scenario, including the materials of the filler phase and the open-cell foam matrix. The filler phase material is a phase change material, preferably paraffin wax; the open-cell foam matrix material is open-cell foam metal, preferably open-cell foam copper. The upper and lower pressure plates are made of the same material, generally high-strength steel, requiring a strength greater than 600 MPa.
[0042] 2.6 The open-cell foam-based interpenetrating phase composite material model, upper pressure plate, and lower pressure plate were analyzed using the explicit dynamic analysis step of the finite element analysis software. The mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model, namely yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, were obtained.
[0043] The third step involves comparing the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model obtained from the finite element analysis process in the second step—yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D—with the mechanical property characterization parameters required by the application environment—yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0—to check whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model meet the requirements of the application environment. For testing the yield strength σ parameter of the open-cell foam-based interpenetrating phase composite material model, refer to section 3.1; for testing the failure stress Q parameter, refer to section 3.2; for testing the elastic modulus E parameter, refer to section 3.3; for testing the energy absorption parameter D parameter, refer to section 3.4.
[0044] 3.1 If σ≥σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the yield strength of the open-cell foam-based interpenetrating phase composite material model is qualified; if σ<σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the yield strength of the open-cell foam-based interpenetrating phase composite material model is unqualified. If it is necessary to continue testing whether the failure stress Q of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to 3.2; if it is necessary to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to 3.3; if it is necessary to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to 3.4; if it is necessary to end the test, proceed to 3.5.
[0045] 3.2 If Q ≥ Q0, it indicates that the failure stress of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the failure stress of the open-cell foam-based interpenetrating phase composite material model is qualified; if Q < Q0, it indicates that the failure stress of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the failure stress of the open-cell foam-based interpenetrating phase composite material model is unqualified. If it is necessary to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to 3.3; if it is necessary to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to 3.4; if it is necessary to end the test, proceed to 3.5.
[0046] 3.3 If E≥E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is qualified; if E<E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is unqualified. If you need to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5.
[0047] 3.4 If D ≥ D0, it indicates that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model meet the application requirements, and the conclusion is that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are qualified; if D < D0, it indicates that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model do not meet the application requirements, and the conclusion is that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are unqualified. (Continue to 3.5)
[0048] 3.5 The test is complete, and the test results are output.
[0049] The mechanical property test results of open-cell foam-based interpenetrating phase composites provide guidance for designers' further work. If the test results meet the application requirements, it indicates that the design of open-cell foam-based interpenetrating phase composites based on the open-cell foam-based interpenetrating phase composite model is reasonable and can be put into production. If the test results do not meet the application requirements, it indicates that the design of open-cell foam-based interpenetrating phase composites based on the open-cell foam-based interpenetrating phase composite model is unreasonable and needs to be improved. Based on the mechanical property characterization parameters of open-cell foam-based interpenetrating phase composites given by the test results, the reasons why the open-cell foam-based interpenetrating phase composites designed according to the open-cell foam-based interpenetrating phase composite model do not meet the application environment requirements should be determined. Further design of open-cell foam-based interpenetrating phase composites should be carried out, and the mechanical properties should be tested again using this invention after the design is completed.
[0050] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0051] (1) In step 1.1 of this invention, the open-cell foam-based interpenetrating phase composite material to be tested is modeled. During testing, the model is designed to match the application scenario. It does not require the actual preparation of the open-cell foam-based interpenetrating phase composite material, nor does it require special experimental equipment or personnel with professional skills. On the one hand, it can save time and labor costs to a great extent and improve testing efficiency. On the other hand, the testing is not affected by factors such as the preparation process of the open-cell foam-based interpenetrating phase composite material, experimental equipment and experimental operation errors, and environment, thus reducing testing errors.
[0052] (2) The open-cell foam-based interpenetrating phase composite material model established by the mechanical property testing method of the present invention takes into account the accuracy of the open-cell foam-based interpenetrating phase composite material compared with the real material in steps 1.6 and 1.7 (e.g., the structural model generated by the structural line model is basically consistent with the real material required). The mechanical property test results obtained by using the present invention to test the mechanical property of the open-cell foam-based interpenetrating phase composite material are more accurate than the mechanical property test results obtained by finite element analysis through simplified model. Attached Figure Description
[0053] Figure 1 This is the overall flowchart of the present invention;
[0054] Figure 2 This is a flowchart of the first step in this invention: establishing a model of an open-cell foam-based interpenetrating phase composite material.
[0055] Figure 3 This is the model diagram constructed in the first step of this invention. Figure 3 (a) is the open-cell foam material matrix constructed in step 1.7 of this invention. Figure 3(b) is the model of the open-cell foam-based interpenetrating phase composite material constructed in step 1.9 of this invention;
[0056] Figure 4 This is a schematic diagram of the second step of the finite element calculation in this invention;
[0057] Figure 5 This is a comparison chart of the mechanical property characterization parameters obtained by testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials using the present invention and the mechanical property characterization parameters obtained by the method described in the background art for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials through experiments. The horizontal axis represents engineering strain and the vertical axis represents engineering stress. Detailed Implementation
[0058] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0059] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0060] This invention discloses a method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials. The overall process is as follows: Figure 1 As shown.
[0061] The first step is to establish a model of the open-cell foam-based interpenetrating phase composite material. The detailed modeling process of the open-cell foam-based interpenetrating phase composite material model is as follows: Figure 2 As shown:
[0062] 1.1 Determine the shape and size of the open-cell foam-based interpenetrating phase composite material model according to the application scenario (such as protection of engines and their key components, power systems, electronic devices, etc.). The maximum area of the open-cell foam-based interpenetrating phase composite material model is greater than or equal to the area of the largest surface of the protected electronic component. Let the volume of the open-cell foam-based interpenetrating phase composite material model determined according to the application scenario be V. m =785.39mm 3 .
[0063] 1.2 Based on the open-cell foam-based interpenetrating phase composite material model, determine the volume V0 of the random porous model and the average number of pores N of the random porous model, and randomly place seed points within the random porous model. The method is as follows:
[0064] The geometry of the random porous model is defined as a cuboid, and its volume is defined as V0. The random porous model must be able to completely contain at least two open-cell foam-based interpenetrating phase composite material models determined according to the application scenario, i.e., V0 ≥ 2V0. m V0 = 1571 mm 3 The average number of open cells per inch (ppi) of the open-cell foam matrix was determined based on the application scenario (ppi was 30 in the example). The average number of pores N = 2589 for the random porous model was determined using formula (1).
[0065]
[0066] 1.3 The number of seed points M in the 3D-Voronoi model is determined by the average number of pores N in the random porous model, i.e., M = N = 2589. (The 3D-Voronoi model is a 3D discretization method based on the Voronoi diagram. It divides the three-dimensional space into a series of polyhedral elements, each containing a discrete point (called a "seed point"). Different foam materials with different structures can be generated by controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral elements. In this example, foam materials are generated by controlling the number of seed points M = 2589.)
[0067] 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model.
[0068] 1.5 A 3D-Voronoi model is established based on seed points randomly placed within the random porous model, and 3D-Voronoi cells are generated from the 3D-Voronoi model.
[0069] In a random porous model, each randomly distributed seed point has a surrounding space called a Voronoi cell. The distance from any point A (excluding the seed point) within a Voronoi cell to the seed point Q within the Voronoi cell is less than the distance from point A to any other seed point in the space (excluding Q). In other words, each Voronoi cell encloses only one seed point. A 3D-Voronoi model is constructed from all Voronoi cells within the random porous model. From the 3D-Voronoi model, a series of 3D-Voronoi cells can be obtained. Each 3D-Voronoi cell corresponds to a seed point in the random porous model and has a different geometry and size.
[0070] 1.6 Extract points and lines from 3D-Voronoi cells to generate a structural line model. The method is as follows:
[0071] 1.6.1 Decompose the 3D-Voronoi cell into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cell.
[0072] 1.6.2 Since adjacent 3D-Voronoi cells in the 3D-Voronoi model are in contact with each other, there are a large number of repeated intersections and lines after the 3D-Voronoi cells are decomposed into points and lines. Therefore, the repeated intersections and lines in the initial structural line model are cleaned up, that is, the repeated points and lines are deleted. The remaining intersections and lines in the initial structural line model constitute the structural line model.
[0073] 1.7 Transform the structural line model into a structural volume model, and obtain the open-cell foam material matrix from the structural volume model. The method is as follows:
[0074] 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number, take d = 0.1 mm, so that the structure line in the structure line model is generated from the line and the structure line model is transformed into a structure model.
[0075] 1.7.2 The volume of the structural model was calculated using the modeling software Rhino (version 6.0) as V = 43.67 mm. 3 .
[0076] 1.7.3 Calculate the theoretical volume V of the open-cell foam matrix using formula (2) n =43.988mm 3 :
[0077] V n =V0×ε (4)
[0078] In the formula, ε represents the relative density of the open-cell foam material matrix, which is equal to 0.028 of the relative density of the open-cell foam material in the model of open-cell foam matrix interpenetrating phase composite material.
[0079] 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam matrix. n To make a comparison, if V n -V>0.5mm 3 This indicates that the volume V of the structural model is smaller than the theoretical volume V. n This requires increasing the diameter d of the structure lines in the structure line model; see section 1.7.1. If V n -V < -0.5mm 3 This indicates that the volume V of the structural model is too large, and the diameter d of the structural lines in the structural line model needs to be reduced. (See 1.7.1) If |Vn -V│≤0.5mm 3 This explains the relationship between the total volume V of the structural model and the theoretical volume V of the open-cell foam material matrix. n If they are approximately equal, then the structural model is the open-cell foam material matrix. In this example, V n -V = 43.988 - 43.67 = 0.318 (mm) 3 ≤0.5mm 3 At this point, the structural model is the open-cell foam material matrix, such as... Figure 3 As shown in (a), the geometry of the open-cell foam matrix is a cuboid, and the open-cell foam matrix has an open-cell ratio of more than 90%, which can fill the pores with phase change material. Under impact load, the cells of the open-cell foam matrix absorb energy during deformation and collapse, and have a certain strength. (See 1.8)
[0080] 1.8 Construct an initial filled phase model with the same geometry and dimensions as the open-cell foam-based interpenetrating phase composite material model.
[0081] 1.9 Place the initial filled phase model at the geometric center of the open-cell foam matrix, remove the material from the open-cell foam matrix outside the initial filled phase model, and remove the material from the portion of the initial filled phase model that overlaps with the open-cell foam matrix to obtain the open-cell foam matrix interpenetrating phase composite material model. For example... Figure 3 As shown in (b), the open-cell foam-based interpenetrating phase composite material model 3 is composed of a filled phase model 31 (the difference from the initial filled phase model is that the material that overlaps with the open-cell foam material matrix in the initial filled phase model is removed) filled in the open-cell foam material matrix 32. The two components, the filled phase model 31 and the open-cell foam material matrix 32, are two separate parts in space, and they run through the entire open-cell foam-based interpenetrating phase composite material model 3. Since the components of the open-cell foam-based interpenetrating phase composite material are interconnected in three-dimensional space and entangled in all directions, the interface volume ratio is quite high, and the open-cell foam-based interpenetrating phase composite material model 3 can meet certain mechanical properties.
[0082] The second step involves performing finite element analysis on the open-cell foam-based interpenetrating phase composite material model 3 constructed in the first step using finite element analysis software (ANSYS version 19.2 in this embodiment). The method is as follows:
[0083] 2.1 To more realistically reflect the stress state of the open-cell foam-based interpenetrating phase composite material model 3, an upper pressure plate 1 is established at the contact point with the upper surface of the open-cell foam-based interpenetrating phase composite material model 3, and a lower pressure plate 2 is established at the contact point with the lower surface of the open-cell foam-based interpenetrating phase composite material model 3, as follows: Figure 4As shown, model 3 of the open-cell foam-based interpenetrating phase composite material is located at the geometric center between the upper pressure plate 1 and the lower pressure plate 2. The upper pressure plate 1 and the lower pressure plate 2 are discs with identical geometric dimensions. The cross-sectional diameter of the upper pressure plate 1 and the lower pressure plate 2 is greater than the cross-sectional diameter of the open-cell foam-based interpenetrating phase composite material matrix, and the thickness has no special requirements.
[0084] 2.2 Finite element mesh generation was performed on the open-cell foam-based interpenetrating phase composite material model 3 and the upper pressure plate 1 and lower pressure plate 2. The open-cell foam-based interpenetrating phase composite material model 3 adopted a tetrahedral mesh, and the upper pressure plate 1 and lower pressure plate 2 adopted a hexahedral mesh. The mesh was evenly distributed on the open-cell foam-based interpenetrating phase composite material model 3, the upper pressure plate 1, and the lower pressure plate 2.
[0085] 2.3 Define the motion boundaries of the upper pressure plate 1 and the lower pressure plate 2, and establish a Cartesian coordinate system as follows: Figure 4 As shown. The upper pressure plate 1 is not allowed to have displacement in the X and Y directions, nor is it allowed to rotate in the X, Y, and Z directions. The upper pressure plate 1 is only allowed to move along the Z direction. At the same time, the lower pressure plate 2 is not allowed to have displacement or rotation in the X, Y, and Z directions.
[0086] 2.4 The contact between the upper pressure plate 1 and the upper surface of the open-cell foam-based interpenetrating phase composite material model 3 is defined as surface-to-surface contact, the contact between the lower pressure plate 2 and the lower surface of the open-cell foam-based interpenetrating phase composite material model 3 is defined as surface-to-surface contact, and the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating phase composite material model 3 is defined as erosion contact.
[0087] 2.5 The materials of the open-cell foam-based interpenetrating phase composite material model 3, the upper pressure plate 1, and the lower pressure plate 2 are determined according to the application scenario. The materials of the open-cell foam-based interpenetrating phase composite material model 3 are determined according to the open-cell foam-based interpenetrating phase composite material required by the application scenario, including the materials of the filling phase and the open-cell foam material matrix. In this embodiment, the filling phase material is paraffin wax; the open-cell foam material matrix material is open-cell foam copper. The upper pressure plate 1 and the lower pressure plate 2 are made of the same material; in this embodiment, high-strength steel with a strength of 650 MPa is used.
[0088] 2.6 The open-cell foam-based interpenetrating phase composite material model 3, upper pressure plate 1, and lower pressure plate 2 were analyzed using the explicit dynamic analysis step of the finite element analysis software. The mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model 3, namely yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D, were obtained.
[0089] The third step involves comparing the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model 3 obtained from the finite element analysis process in the second step—yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D—with the mechanical property characterization parameters required by the application environment—yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0—to check whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model meet the requirements of the application environment. For testing the yield strength σ of the open-cell foam-based interpenetrating phase composite material model, refer to section 3.1; for testing the failure stress Q of the open-cell foam-based interpenetrating phase composite material model, refer to section 3.2; for testing the elastic modulus E of the open-cell foam-based interpenetrating phase composite material model, refer to section 3.3; for testing the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material model, refer to section 3.4.
[0090] 3.1 If σ≥σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the yield strength of the open-cell foam-based interpenetrating phase composite material model is qualified; if σ<σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the yield strength of the open-cell foam-based interpenetrating phase composite material model is unqualified. If you need to continue testing whether the failure stress Q of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.2; if you need to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.3; if you need to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5.
[0091] 3.2 If Q ≥ Q0, it indicates that the failure stress of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the failure stress of the open-cell foam-based interpenetrating phase composite material model is qualified; if Q < Q0, it indicates that the failure stress of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the failure stress of the open-cell foam-based interpenetrating phase composite material model is unqualified. If you need to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.3; if you need to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5.
[0092] 3.3 If E≥E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is qualified; if E<E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is unqualified. If you need to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, go to 3.4; if you need to end the test, go to 3.5;
[0093] 3.4 If D ≥ D0, it indicates that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model meet the application requirements, and the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are considered qualified; if D < D0, it indicates that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model do not meet the application requirements, and the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are considered unqualified. End the test, go to 3.5;
[0094] 3.5 The test is complete, and the test results are output.
[0095] To verify the accuracy and high detection efficiency of this invention, the mechanical properties of the open-cell foam-based interpenetrating phase composite material described in Example 1 of this invention were experimentally tested. The experimental results were compared with the test results of this invention. The methods for detecting the mechanical property characterization parameters—yield strength, failure stress, elastic modulus, and energy absorption parameters—in the third step are basically the same. The effect can be illustrated by taking yield strength and energy absorption parameters as examples. Through steps 2.6, the open-cell foam-based interpenetrating phase composite material of the example was obtained at a strain rate of 1700 s⁻¹. -1 The yield strength σ is 12.2 MPa, and the mechanical property index of the yield strength σ0 is 10.0 MPa. Since σ ≥ σ0, the yield strength of the open-cell foam-based interpenetrating phase composite material model is considered to be qualified.
[0096] With a strain rate of 1700s -1 The results obtained from the experiments and the present invention are plotted together in Figure 5 middle, Figure 5The black curve represents the test results of this invention, and the red curve represents the test results of the experimental method. The horizontal axis represents engineering strain, and the vertical axis represents engineering stress. During the operation of the experimental equipment, due to improper clamping of the experimental apparatus, there is a large systematic error, resulting in a difference between the red and black curves when the engineering strain is below 0.15. The main mechanical performance index of this invention is yield strength (i.e., the engineering stress corresponding to an engineering strain of 0.15), and it can be seen that the accuracy of this invention is good. Furthermore, comparing the energy absorption parameters (i.e., the area enclosed by engineering stress and engineering strain within the engineering strain range of 0-0.3, representing the energy absorption parameter) of the test results of this invention and the experimental method, it can be seen that the test results of this invention are approximately equal to those of the experimental method, demonstrating good accuracy and qualitative determination. Therefore, using this invention to experimentally test the mechanical properties of open-cell foam-based interpenetrating phase composite materials yields test results with accuracy comparable to those of the experimental method. The comparison between the test results of failure stress and elastic modulus and the experimental results is as follows... Figure 5 They are basically the same, so I won't go into details.
[0097] When testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials using experimental methods, the entire process, from material preparation to final experiment completion, takes 8 hours. Furthermore, three defective open-cell foam-based interpenetrating phase composite materials are generated during the preparation process. Additionally, improper clamping of the experimental equipment leads to significant systematic errors during operation. In contrast, this invention reduces the entire process to just 1 hour, eliminates defective products, and significantly improves testing efficiency while saving costs.
[0098] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0099] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials, characterized in that... Includes the following steps: The first step is to establish a model of an open-cell foam-based interpenetrating phase composite material. The method is as follows: Step 1.1 Determine the shape and size of the open-cell foam-based interpenetrating phase composite material model according to the application scenario. The maximum area of the open-cell foam-based interpenetrating phase composite material model is greater than or equal to the area of the largest surface of the protected electronic component. Let the volume of the open-cell foam-based interpenetrating phase composite material model determined according to the application scenario be V. m ; Step 1.2 Determine the volume V0 of the random porous model and the average number of pores N of the random porous model based on the open-cell foam-based interpenetrating phase composite material model, and randomly place seed points in the random porous model. Step 1.3 Determine the number of seed points M of the 3D-Voronoi model by the average number of pores N of the random porous model, that is, let M=N; the 3D-Voronoi model divides the three-dimensional space into a series of polyhedral units, each unit contains a discrete point, namely the "seed point". By controlling the number of seed points M, the minimum distance between seed points, and the wall thickness of the polyhedral units, foam materials with different structures are generated. Step 1.4 Randomly arrange M seed points in the random porous model to fill the entire random porous model; Step 1.5: Construct a 3D-Voronoi model based on randomly distributed seed points within the random porous model, and generate 3D-Voronoi cells from the 3D-Voronoi model. Each randomly distributed seed point within the random porous model has a space nearby, called a Voronoi cell, and each Voronoi cell encloses a seed point. Construct a 3D-Voronoi model from all Voronoi cells within the random porous model, and obtain a series of 3D-Voronoi cells from the 3D-Voronoi model. Each 3D-Voronoi cell corresponds to a seed point in the random porous model and has a different geometry and size. Step 1.6 Extract the points and lines of 3D-Voronoi cells to generate a structural line model; Step 1.7 transforms the structural line model into a structural body model, from which the open-cell foam material matrix is obtained; Step 1.8 Construct an initial filled phase model with the same geometry and dimensions as the open-cell foam-based interpenetrating phase composite material model; Step 1.9 Place the initial filled phase model at the geometric center of the open-cell foam matrix, remove the material of the open-cell foam matrix outside the initial filled phase model, and remove the material of the initial filled phase model that overlaps with the open-cell foam matrix to obtain the open-cell foam matrix interpenetrating phase composite material model (3); the open-cell foam matrix interpenetrating phase composite material model (3) is composed of the filled phase model (31) filled in the open-cell foam matrix (32). The two components, the filled phase model (31) and the open-cell foam matrix (32), are two separate parts in space, and they run through the entire open-cell foam matrix interpenetrating phase composite material model (3); the difference between the filled phase model (31) and the initial filled phase model is that the material of the part of the initial filled phase model that overlaps with the open-cell foam matrix (32) has been removed; The second step involves using finite element analysis software to perform finite element analysis on the open-cell foam-based interpenetrating phase composite material model (3) constructed in the first step. The method is as follows: Step 2.1 Establish an upper pressure plate (1) at the contact point with the upper surface of the open-cell foam-based interpenetrating phase composite material model (3), and establish a lower pressure plate (2) at the contact point with the lower surface of the open-cell foam-based interpenetrating phase composite material model (3). The open-cell foam-based interpenetrating phase composite material model (3) is located at the geometric center between the upper pressure plate (1) and the lower pressure plate (2). The upper pressure plate (1) and the lower pressure plate (2) are disks with identical geometric dimensions. The cross-sectional diameter of the upper pressure plate (1) and the lower pressure plate (2) is greater than the cross-sectional diameter of the open-cell foam-based interpenetrating phase composite material matrix. Step 2.2 Perform finite element mesh generation on the open-cell foam-based interpenetrating phase composite material model (3) and the upper pressure plate (1) and lower pressure plate (2). The open-cell foam-based interpenetrating phase composite material model (3) adopts a tetrahedral mesh, and the upper pressure plate (1) and lower pressure plate (2) adopt a hexahedral mesh. The mesh is evenly distributed on the open-cell foam-based interpenetrating phase composite material model (3), the upper pressure plate (1) and the lower pressure plate (2). Step 2.3 Constrain the motion boundaries of the upper pressure plate (1) and the lower pressure plate (2), establish a Cartesian coordinate system, and do not allow the upper pressure plate (1) to have displacement in the X and Y directions, nor do they allow the upper pressure plate (1) to have rotation in the X, Y, and Z directions. Only the upper pressure plate (1) is allowed to move along the Z direction, while the lower pressure plate (2) is not allowed to have displacement and rotation in the X, Y, and Z directions. Step 2.4 Define the contact between the upper pressure plate (1) and the upper surface of the open-cell foam-based interpenetrating phase composite material model (3) as surface-to-surface contact, define the contact between the lower pressure plate (2) and the lower surface of the open-cell foam-based interpenetrating phase composite material model (3) as surface-to-surface contact, and define the contact between the open-cell foam material and the filling phase material in the open-cell foam-based interpenetrating phase composite material model (3) as erosion contact. Step 2.5 Determine the materials of the open-cell foam-based interpenetrating phase composite material model (3), upper pressure plate (1), and lower pressure plate (2) according to the application scenario. The material of the open-cell foam-based interpenetrating phase composite material model (3) is determined according to the open-cell foam-based interpenetrating phase composite material required by the application scenario, including the material of the filling phase and the material of the open-cell foam material matrix. The material of the filling phase is a phase change material, and the material of the open-cell foam material matrix is open-cell foam metal. The materials of the upper pressure plate (1) and the lower pressure plate (2) are the same, and high-strength steel is used. Step 2.6 The open-cell foam-based interpenetrating phase composite material model (3), upper pressure plate (1) and lower pressure plate (2) are subjected to finite element analysis using the display dynamic analysis step of the finite element analysis software to obtain the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model (3), namely yield strength σ, failure stress Q, elastic modulus E and energy absorption parameter D. The third step involves comparing the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model (3) obtained through the finite element analysis process in the second step—yield strength σ, failure stress Q, elastic modulus E, and energy absorption parameter D—with the mechanical property characterization parameters required by the application environment—yield strength σ0, failure stress Q0, elastic modulus E0, and energy absorption parameter D0—to check whether the mechanical property characterization parameters of the open-cell foam-based interpenetrating phase composite material model meet the requirements of the application environment. If it is necessary to check the yield strength σ of the open-cell foam-based interpenetrating phase composite material model, proceed to step 3.1; if it is necessary to check the failure stress Q of the open-cell foam-based interpenetrating phase composite material model, proceed to step 3.2; if it is necessary to check the elastic modulus E of the open-cell foam-based interpenetrating phase composite material model, proceed to step 3.3; if it is necessary to check the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material model, proceed to step 3.
4. Step 3.1 If σ≥σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the yield strength of the open-cell foam-based interpenetrating phase composite material model is qualified; if σ<σ0, it indicates that the yield strength of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the yield strength of the open-cell foam-based interpenetrating phase composite material model is unqualified; if it is necessary to continue testing whether the failure stress Q of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.2; if it is necessary to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.3; if it is necessary to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.4; if it is necessary to end the test, proceed to step 3.
5. Step 3.2 If Q≥Q0, it means that the failure stress of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the failure stress of the open-cell foam-based interpenetrating phase composite material model is qualified. If Q < Q0, it indicates that the failure stress of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the failure stress of the open-cell foam-based interpenetrating phase composite material model is unqualified. If it is necessary to continue testing whether the elastic modulus E of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.
3. If it is necessary to continue testing whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.
4. If it is necessary to end the test, proceed to step 3.
5. Step 3.3 If E≥E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model meets the application requirements, and the conclusion is that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is qualified; if E<E0, it indicates that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model does not meet the application requirements, and the conclusion is that the elastic modulus of the open-cell foam-based interpenetrating phase composite material model is unqualified; if it is necessary to continue to test whether the energy absorption parameter D of the open-cell foam-based interpenetrating phase composite material meets the application requirements, proceed to step 3.4; if it is necessary to end the test, proceed to step 3.
5. Step 3.4 If D≥D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model meet the application requirements, and the conclusion is that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are qualified. If D < D0, it means that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model do not meet the application requirements, and the conclusion is that the energy absorption parameters of the open-cell foam-based interpenetrating phase composite material model are unqualified; proceed to step 3.
5. Step 3.5 The detection is complete, and the detection results are output.
2. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 1, characterized in that... Step 1.2 describes the method for determining the volume V0 of the random porous model and the average number of pores N of the random porous model based on the open-cell foam-based interpenetrating phase composite material model, and for randomly placing seed points within the random porous model: the geometry of the random porous model is determined to be a cuboid, and the volume of the random porous model is defined as V0, requiring V0 ≥ 2V m The average number of open cells per inch (ppi) of the open-cell foam matrix is determined according to the application scenario, and the average number of pores (N) of the random porous model is determined by formula (1): Official (1).
3. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 2, characterized in that... The ppi is 20~100.
4. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 1, characterized in that... The method described in step 1.6 for extracting points and lines from 3D-Voronoi cells to generate a structural line model is as follows: Step 1.6.1 Decompose the 3D-Voronoi cell into points and lines, and generate an initial structural line model based on the points and lines decomposed from the 3D-Voronoi cell. Step 1.6.2 Clean up the duplicate intersections and lines in the initial structural line model, that is, delete the duplicate points and lines. The remaining intersections and lines in the initial structural line model constitute the structural line model.
5. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 1, characterized in that... Step 1.7 describes the method of transforming the structural line model into a structural volume model, and obtaining the open-cell foam material matrix from the structural volume model: Step 1.7.1 Initialize the diameter d of the structure line in the structure line model to any positive number. In this way, the structure line in the structure line model is transformed from a line to a volume, and the structure line model is transformed into a structure volume model. Step 1.7.2 Use the modeling software Rhino 6.0 or later to calculate the volume V of the structural model; Step 1.7.3 Calculate the theoretical volume V of the open-cell foam material matrix using formula (2). n : Official (2); In the formula, ε represents the relative density of the open-cell foam material matrix, which is equal to the relative density of the open-cell foam material in the model of open-cell foam matrix interpenetrating phase composite material; It is the volume of the random porous model; Step 1.7.4 Compare the volume V of the structural model with the theoretical volume V of the open-cell foam material matrix. n To make a comparison, if V n -V>0.5mm 3 This indicates that the volume V of the structural model is smaller than the theoretical volume V. n To increase the diameter d of the structural lines in the structural line model, proceed to step 1.7.1; if V n -V < -0.5mm 3 This indicates that the volume V of the structural model is too large, and the diameter d of the structural lines in the structural line model needs to be reduced. Proceed to step 1.7.1; if |V n -V│≤0.5mm 3 This explains the relationship between the total volume V of the structural model and the theoretical volume V of the open-cell foam material matrix. n If they are approximately equal, then the structural model is the open-cell foam material matrix.
6. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 1, characterized in that... The finite element analysis software mentioned in the second step is ANSYS or ABAQUS. ANSYS requires version 19.2 or above, and ABAQUS requires version 6.14 or above.
7. The method for testing the mechanical properties of open-cell foam-based interpenetrating phase composite materials as described in claim 1, characterized in that... The filling phase material in step 2.5 is paraffin wax; the material of the open-cell foam material matrix is open-cell foam copper; the high-strength steel used in the upper pressure plate (1) and lower pressure plate (2) is required to have a strength greater than 600 MPa.